PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING (GBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS MATA PELAJARAN IPAS KELAS V SD NEGERI BESKALAN SURAKARTA TAHUN PELAJARAN 2025/2026 - Jihan Salsabela, Fanisia; Heru Sri Suryanti, Hera; Hastini, Dite (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is based on the observation of the low critical thinking skills of fifth-grade students in science learning, which is characterized by low participation, activeness, and suboptimal learning outcomes due to the use of conventional learning models. This study aims to analyze the impact of the application of the Game Based Learning (GBL) learning model on students' critical thinking skills. The method used is a quantitative approach with a pre-experimental research type using a one-group pre-test post-test design. The research subjects were 33 fifth-grade students of Beskalan Surakarta Elementary School in the 2025/2026 academic year. Data collection was carried out through tests, observations, interviews, and documentation. Data were analyzed using a paired sample t-test to compare the results before and after treatment. The results showed an increase in the average score from 64.82 in the pre-test to 78.45 in the post-test. The statistical test showed a significant value of 0.000 <0.05, indicating that there was a significant influence of the use of the Game Based Learning model on students' critical thinking skills. So it can be concluded that the Game Based Learning model has proven effective in improving critical thinking skills in science learning.